Rounding in the problem of the allocation of indivisible goods - Cegiełka, Katarzyna; Łyko, Janusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Using approximate, rounded values implies, in a sense, that an exact numerical value may be ignored. In many cases the difference between the exact and approximate values is not important, and replacing exact numbers by their approximate values does not result in undesired consequences. Yet in certain circumstances, rounding significantly influences the solutions of given problems. This is the case, among others, when we allocate indivisible goods. It may happen that the rounding mode affects the result of allocation so much that the rounding differences cannot be neglected by the agents participating in distribution. This paper presents the classic problem of distributing mandates in representative bodies along with different rounding modes in respective solution procedures
Didactics of Mathematics, 2017, Nr 14 (18), s. 5-18
Keywords: rounding rule; approximation; allocation problem; indivisible goods